Clinicopathological characteristics and predictors of renal outcomes in diffuse crescentic glomerulonephritis : a retrospective single-center study from Western China - Shan Wen; Shasha Chen; Yingying Lin; Guisen Li; Ping Zhang; Wei Wang (BMC Nephrology)
Abstract Background The factors influencing diffuse crescentic glomerulonephritis renal survival and prognosis remain uncertain. Additionally, there’s no literature on the clinical outcomes of IgA nephropathy, lupus nephritis, and IgA vasculitis nephritis in type II patients. Methods This study retrospectively examined 107 patients diagnosed with diffuse crescentic glomerulonephritis through biopsy. Analytical methods included Cox regression models and Kaplan-Meier survival analysis to assess the data. Results Among the 107 enrolled patients, 12 patients had Type I diffuse crescentic glomerulonephritis, 70 patients had Type II, and 25 patients had Type III. The respective 5-year kidney survival rates were 0%, 57.5%, and 18.6% for type I, type II, and type III. Furthermore, among Type II patients, IgA nephropathy emerged as the most prevalent condition. The cumulative 5-year kidney survival rates were 50% for patients with IgA nephropathy, 64% for lupus nephritis, and 70% for Henoch-Schönlein purpura nephritis. A significant association between the risk of ESKD development and several factors was revealed by a multivariate Cox regression analysis: estimated glomerular filtration rate (P = 0.004), initial kidney replacement therapy (KRT) at presentation (P = 0.002), global glomerulosclerosis (P<0.001). Conclusions Type II diffuse crescentic glomerulonephritis was the most prevalent type in DCGN, and favors better renal prognosis than type I and III DCGN, in which IgA nephropathy was the most common entity of Type II DCGN. Additionally, estimated glomerular filtration rate, initial KRT at presentation and global glomerulosclerosis were identified as predictors of renal outcomes in diffuse crescentic glomerulonephritis.